Optimization of dye mixing for achromatic transmittance control with a dye-doped cholesteric liquid crystal cell. (January 2019) - Ji, Seong-Min; Oh, Seung-Won; Jo, Young-Seo; Nam, Seung-Min; Kim, Sang-Hyeok; Huh, Jae-Won; Lim, Eunjung; Kim, Jinhong; Yoon, Tae-Hoon
Abstract: Transmittance-control liquid crystal (LC) devices require a high transmittance difference between their transparent and opaque states. Dye-doped cholesteric LC (CLC) cells have been widely used for transmittance control because they provide the highest transmittance difference among LC modes. However, the color of a CLC cell is different from that of a homogeneously-aligned LC cell. In this paper, we present a systematic approach to find the optimal dye concentrations for the desired black color in a dye-doped CLC cell. To achieve the desired black color in a dye-doped CLC cell, we consider its transmission spectrum in our numerical calculations. The optimal concentration for each individual dye is found through an iterative process. We demonstrate that a dye-doped CLC cell designed by considering its transmission spectrum can provide a true black color in the CIE 1931 color space. Highlights: We present a systematic approach to find the optimal dye concentrations for the desired black color in a dye-doped CLC cell. It offers an effective method for the fabrication of transmittance-control LC device. To find the optimal dye concentrations, we considered the transmission spectrum of a dye-doped CLC cell.